Potential role of skeletal muscle glucose metabolism on the regulation of insulin secretion. Issue 7 (11th March 2014) - Mizgier, M. L.; Casas, M.; Contreras‐Ferrat, A.; Llanos, P.; Galgani, J. E.
Summary Pancreatic beta cells sense glucose flux and release as much insulin as required in order to maintain glycaemia within a narrow range. Insulin secretion is regulated by many factors including glucose, incretins, and sympathetic and parasympathetic tones among other physiological factors. To identify the mechanisms linking obesity‐related insulin resistance with impaired insulin secretion represents a central challenge. Recently, it has been argued that a crosstalk between skeletal muscle and the pancreas may regulate insulin secretion. Considering that skeletal muscle is the largest organ in non‐obese subjects and a major site of insulin‐ and exercise‐stimulated glucose disposal, it appears plausible that muscle might interact with the pancreas and modulate insulin secretion for appropriate peripheral intracellular glucose utilization. There is growing evidence that muscle can secrete so‐called myokines that can have auto/para/endocrine actions. Although it is unclear in which direction they act, interleukin‐6 seems to be a possible muscle‐derived candidate protein mediating such inter‐organ communication. We herein review some of the putative skeletal muscle‐derived factors mediating this interaction. In addition, the evidence coming from in vitro, animal and human studies that support such inter‐organ crosstalk is thoroughly discussed.